Analisis Dan Perancangan Sistem Presensi Karyawan PT Berkah Untuk Semesta - Satriyo Rizkyansah; Muhammad Tri Putro Alfaz Dzikri (Journal of Information Systems and Business Technology, 2025)
This study aims to design and develop a web-based employee attendance system at PT Berkah Untuk Semesta to replace the manual method that has been used so far. This system is built using the Laravel framework and run locally using Laragon. With the implementation of this system, the attendance process becomes more efficient, accurate, and transparent, and supports better data-based decision making. This system is expected to be able to increase the effectiveness of attendance management and reduce the potential for errors that often occur in manual recording.